Factors Are Affecting Tais Timor Consumers Purchase Decision in Alola Esperansa - Filomena da Costa; Luh Komang Chandra Dewi; Augusto da Conceição (ABM: International Journal of Administration, Business and Management, 2020)
This study aims to analyze and explain: (1) To know and explain what factors influence consumer-purchasing decisions; (2) To find out and explain what factors are dominant in influencing consumer purchasing decisions; (3) to find out and explain what factors need to be improved in consumer purchasing decisions.The samples in this study were 80 of all customers or consumers of Alola Esperansa who had shopped Tais Timor at the Alola Esperansa Shop. Questionnaires were distributed to Alola Esperansa 80 consumers and all returned. The findings of this study indicate that the quality factor has the highest eigenvalue value of 5.218 and is able to explain the total variance of 32.612%. The most dominant factor that consumers consider in buying Tais Timor at Alola Esperansa is the Quality Factor. Keywords: Quality Factor, consumer, purchasing decisions